NOVEL EXPERIENCE WITH COMBINED FIX-DOSE THERAPY FOR HYPERTENSION - Trjacheski, Ted (Journal of Morphological Sciences; Vol 2 No 2 (2019): JMS, 2019)
In spite of the general improvement in treatment strategy and novel medications for hypertension, still there are many patients with unsatisfactory results. In this study we retrospectively analyzed the local registry for 280 hypertension patients, referred during 18 months. Aims: To access the efficacy and safety of combined fix-dose therapy approach. Patients were grouped according to the number of antihypertensive medications and mono or fix-combined therapy and followed for 1 month in respect of obtaining target blood pressure control. Patients were informed about taking proper measurements and in respect of drug side effects. Clinical data on previous medical history findings were obtained. Statistical analysis was performed using SPSS 23.0 software package. Parameters were expressed as mean Â± SD and percentages for nominal values. Comparative analysis was performed using X 2  test.Statistical significance was set at p<0.05.Results: The mean age of study participants was over 60 years and there were 47 percentage of men. Obesity was present in almost 20% and quarter were active smokers.Most of the patients were in stage 1 (40%), 37% were in stage 3. The most of the patients and nearly half of all, were treated with fix-dose combined therapy, exporting 48%. Dual therapy with two separate pills was applied in 34% and with only one medicament were treated 16% of patients. The triple therapy was given to only 2% of patients. Patients treated with fix-dose combined therapy were compared with all other patients treated with mono, dual or triple therapy. The two groups of patients did not differ in respect of presence of Diabetes (p=0.676). Those treated with fix combinations were significantly younger (p=0.045), less male (0.001), more burdened with obesity (p=0.028) and more frequently smokers (p= 0.0001). After one month in 95% of patients the blood pressure reached the recommended targets. In 5% the follow up was not completed. Considering drug side effects, three patients treated with mono ACE therapy complained of dry cough and the treatment was replaced with a propriate dose medicament. Conclusion: Combined fox-dose therapy is shown to be of high efficacy and safety in patients with poor control of hypertension, especially in patients with low therapy adherence and at higher cardiovascular risk.